Pharmacokinetic/pharmacodynamic modeling of 5‐fluorouracil by using a biomarker to predict tumor growth in a rat model of colorectal cancer. Issue 6 (16th April 2013) - Kobuchi, Shinji; Ito, Yukako; Okada, Kae; Imoto, Kazuki; Kuwano, Shota; Takada, Kanji
Abstract We developed a pharmacokinetic/pharmacodynamic (PK/PD) model with the value of the plasma ratio of dihydrouracil (UH2)/uracil (Ura), which is a possible surrogate biomarker of hepatic dihydropyrimidine dehydrogenase activity, determined before 5‐fluorouracil (5‐FU) treatment to simulate the growth of tumors after 5‐FU treatment in rats with colorectal cancer (CRC). In the PK/PD model, the value of the elimination rate constant of 5‐FU—ke—was estimated using the plasma UH2/Ura ratio observed before 5‐FU treatment for simulating PKs of 5‐FU and tumor growth. The PK/PD model with plasma UH2/Ura ratio effectively captured the features of tumor growth and the anticancer effect of 5‐FU treatment, which provided reliable parameter estimates. In addition to an appropriate dosing regimen, pretherapeutic assessment of the UH2/Ura ratio in the plasma of CRC patients and PK/PD analysis with the plasma UH2/Ura ratio could enable the development of an optimal therapeutic scheme for each patient. © 2013 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 102:2056–2067, 2013